(untitled) (Journal of Information Technologies in Education (ITE), 2011)
The paper presents an integrated environment for studying the course «Basics of algorithmization and programming» (http://weboap.ksu.ks.ua), which solves the problem of improving the efficiency of studying this important discipline. We describe the design and development of new version of the program demonstration environment, which allows execution of computational experiments to study the complexity and majorizability of sorting algorithms. Much attention is paid to the development component of the code editor. An architectural design strategy was formed. It determines the solution components and their interactions. The paper describes the technologies and products which were selected as a means for implementing solutions.